THE NEED FOR A LEGAL DEFINITION OF STATELESS CHILDREN IN MALAYSIAN NATIONAL LAW AND POLICY: THE PERSPECTIVE FROM INTERNATIONAL HUMAN RIGHTS LAW (UUM Journal of Legal Studies, 2022)
Millions of people worldwide remain stateless with various breakdowns in many regions (UN, 2018). As of 2019, the United Nations High Commissioner for Refugees (hereinafter UNHCR) estimated a total of 3.9 million stateless people in the world (UNHCR, Malaysia, 2019). According to the United Nations (UN, 2018), approximately 50 percent of the 10 million stateless people of the world are residing in Asia, with at least 1 million of them being Rohingya Muslims from Myanmar. Amongst the member states of the Association of South East Asian Nations (ASEAN), countries like Thailand, Indonesia and Malaysia continuously face challenges pertaining to statelessness and stateless children. They usually come from neighbouring countries like Bangladesh and Myanmar (SUHAKAM, 2018). This article therefore, will examine the challenges of these statelessness and stateless children in Malaysia from a legal perspective; particularly on the definitions, categories of stateless children and the importance for the country to have national laws and policies pertaining to these issues.